Edukasi Sampah Di SDN Karanggintung 1 Dan 2 Kelas V Desa Karanggintung Tahun 2023 - Dian Imam Saefulah; Ari Gana Yuliana; Farhan Ramadhan (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Thematic Real Work Lectures (KKN) are KKN whose activity programs focus on certain areas according to social problems and the direction of development policies implemented by certain regional governments. STKIP Darussalam Cilacap organizes a Real Work Lecture program using the thematic method. KKN-T is intended to develop a spirit of empathy and concern for problems that occur in society. KKN-T was implemented in several villages, one of which was Rawaapu Village, Patimuan District, Cilacap Regency. The results achieved after implementing this Waste Education Program are increasing children's understanding of waste and how to use it. This of course also indirectly increases students' awareness of the waste crisis that has occurred. The uses for this recycled waste product include making elcobricks and also making flower pots. This is to increase children's awareness and to encourage children to be able to make and develop recycled products from waste. Especially non-organic waste which takes a very long time to decompose